3D kinematical analysis of brazilian female pole vaulters - Russomanno, T.; Rossetto, N.; Barros, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Pole Vault is one of the most technical events in track and field. Schade et al. (2005) evaluated kinematical and dynamic variables during the 2005 World Championship in Helsinki providing data of world class vaulters for comparison. Recently, Brazilian pole vaulters have obtained world class results but, despite this, no biomechanical analysis has been conducted with such athletes. Therefore, the aim of this work is the 3D kinematical analysis of the best female athletes during the "XXVII Brazilian Trophy" in 2008.